2021
DOI: 10.3390/cancers13051005
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Activated Lung Stromal Cells Promote Myeloid Lineage Cell Accumulation and Breast Cancer Metastasis

Abstract: Obesity is correlated with increased incidence of breast cancer metastasis; however, the mechanisms underlying how obesity promotes metastasis are unclear. In a diet-induced obese mouse model, obesity enhanced lung metastasis in both the presence and absence of primary mammary tumors and increased recruitment of myeloid lineage cells into the lungs. In the absence of tumors, obese mice demonstrated increased numbers of myeloid lineage cells and elevated collagen fibers within the lung stroma, reminiscent of pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
3
7
0
Order By: Relevance
“…Several leptin-mediated mechanisms behind this link have been established, including breast cancer invasion, migration, and immune regulation [46,47], as well as cancer stem cell enrichment and mesenchymal stem cell dysregulation in the tumor microenvironment [31,48]. Preclinical models of obesity demonstrate that increased myeloid-derived suppressor cell (MDSC) recruitment, collagen deposition, and changes in fibroblast phenotype in the lungs cooperate to create a favorable premetastatic niche for breast cancer [49].…”
Section: Obesity and Metastatic Progression Of Breast Cancermentioning
confidence: 99%
“…Several leptin-mediated mechanisms behind this link have been established, including breast cancer invasion, migration, and immune regulation [46,47], as well as cancer stem cell enrichment and mesenchymal stem cell dysregulation in the tumor microenvironment [31,48]. Preclinical models of obesity demonstrate that increased myeloid-derived suppressor cell (MDSC) recruitment, collagen deposition, and changes in fibroblast phenotype in the lungs cooperate to create a favorable premetastatic niche for breast cancer [49].…”
Section: Obesity and Metastatic Progression Of Breast Cancermentioning
confidence: 99%
“…Women had a higher risk of cancer incidence at endometrial, uterine, kidney, and breast sites, but only endometrial cancer mortality was significantly associated with being overweight and centrally obese [ 3 ]. Biological mechanisms behind the major role of obesity in chronic inflammation and carcinogenesis have been extensively assessed [ 4 , 5 , 6 , 7 ]. On the other hand, a population-based cohort study on BMI and the risk of 22 specific cancers in 5.24 million UK adults, showed that BMI was associated with 17 of 22 cancers, but the effect varied substantially by cancer type; each 5 kg/m² increase in BMI was linearly associated with cancers of the uterus, gallbladder, kidney, cervix, thyroid, and leukemia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these types, an inverse relationship between obesity and lung cancer risk has been reported in previous studies (6)(7)(8)(9). And the biological mechanisms underlying the major role of obesity in chronic inflammation and carcinogenesis have also been extensively evaluated (4,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 93%